Management of Nutrition in Forests Under Stress 1991
DOI: 10.1007/978-94-011-3252-7_41
|View full text |Cite
|
Sign up to set email alerts
|

A New Fertilization Strategy in Declining Forests

Abstract: A~stract.In central Europe and to some degree in North America, the so called "new type" forest d~ages occur over large areas. Various studies indicate the declines are more or less frequently associated with nutritional disturbances that have developed within rather short time periods. The most common disorder is a Mg deficiency that produces specific discoloration symptoms such as tip-yellowing in Norway spruce. But also K deficiencies and other disturbances exist in coniferous as well as in deciduous forest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0
2

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 25 publications
1
11
0
2
Order By: Relevance
“…The symptoms of Mg 2+ deficiency in forest plantations and the study of appropriate rates of Mg fertiliser have been investigated since the 1980s in various regions of Germany (EVERS; HÜTTL, 1990;HÜTTL, 1989;ZÖTTL, 1993;UEBEL;HEINSDORF, 1997). In a review paper on conifer plantations in Germany, Hüttl and Zöttl (1993) concluded that the application of Mg 2+ through liming was effective at increasing the Mg level in the soil and reversing the nutrient deficiency symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…The symptoms of Mg 2+ deficiency in forest plantations and the study of appropriate rates of Mg fertiliser have been investigated since the 1980s in various regions of Germany (EVERS; HÜTTL, 1990;HÜTTL, 1989;ZÖTTL, 1993;UEBEL;HEINSDORF, 1997). In a review paper on conifer plantations in Germany, Hüttl and Zöttl (1993) concluded that the application of Mg 2+ through liming was effective at increasing the Mg level in the soil and reversing the nutrient deficiency symptoms.…”
Section: Resultsmentioning
confidence: 99%
“…Soil conditions have been improved, acidity and the amount of free Al ions have been reduced. Wood ash and nonnitrogenous fertilizers are applied to improve the nutrient status [9]. Trees have nutrient reserves in the trunk which are used during the vegetative period, thus soil treatment is not expected to change their nutrient status within a short period [14].…”
Section: Introductionmentioning
confidence: 99%
“…Leaching of nutrients from needles and increased soil acidification which causes leaching of nutrients from the soil may contribute to nutrient imbalance in trees [13,28]. Increased growth, in response to increases in N availability, may induce deficiencies in other nutrients as a result of dilution effects [1].…”
Section: Introductionmentioning
confidence: 99%
“…The cause of this reduction in tree nutritional status is not clear but high N deposition and soil acidification in the area are considered to be the major factors [21]. To counteract nutrient deficiencies or imbalances in trees, vitality fertilization with ash and different types of mineral fertilizers can be carried out [13,30].…”
Section: Introductionmentioning
confidence: 99%